Anonymous

# How do I solve "5x + 2 = 6 - 3x"?

### 5 Answers

Relevance

- 8 years agoBest Answer
Start by getting your all your like terms on the same side of the equation, and then combine them. You might want to combine the variables on one side, and the constants on the other. Then look at your multiplicative inverse property to see if it might help isolate the variable.

If you need more help, please clarify where you are in the process and what's giving you trouble. I'd be more than happy to continue to assist.

- DuckLv 78 years ago
5x + 2 = 6 - 3x

5x + 2 + 3x = 6 - 3x + 3x (add 3x to both sides)

8x + 2 = 6

8x + 2 - 2 = 6 - 2 (subtract 2 from both sides)

8x = 4

8x/8 = 4/8 (divide both sides by 8)

x = 4/8 = 1/2

- ZarnLv 78 years ago
How do you solve?

Well, do this:

Add 3x to both sides:

8x + 2 = 6

Subtract 2 from both sides:

8x = 4

Divide both sides by 8:

x = 4 / 8 = 1 / 2

- How do you think about the answers? You can sign in to vote the answer.

Still have questions? Get your answers by asking now.